Preaching to the choir? Rhetoric and identity in a polarized age - Goodman, R; Bagg, S (University of Chicago Press, 2021)
How might discourse generate political change? So far, democratic theorists have focused largely on how deliberative exchanges might shift political opinion. Responding to empirical research that casts doubt on the generalizability of deliberative mechanisms outside of carefully designed forums, this essay seeks to broaden the scope of discourse theory by considering speech that addresses participants’ identities instead. More specifically, we ask what may be learned about identity-oriented discourse by examining the practice of religious preaching. As we demonstrate, scholars of homiletics—the study of preaching—have identified three core features that support its focus on identity: its unconditionality, its appeal to authoritative texts and traditions, and its diffuse instrumentality. We then ask what each of these features might look like in more straightforwardly political contexts. Finally, we address several normative questions raised by this practice, as a way of exploring the promises and dangers accompanying identity-oriented discourse more generally.